2019
DOI: 10.1097/tme.0000000000000250
|View full text |Cite
|
Sign up to set email alerts
|

Orolingual Angioedema After Tissue Plasminogen Activator Administration in Patients Taking Angiotensin-Converting Enzyme Inhibitors

Abstract: Orolingual angioedema is a rare adverse effect (1%–5%) of tissue plasminogen activator (tPA) that can lead to significant morbidity in patients with acute ischemic stroke. It is thought that increased levels of bradykinin and histamine resulting from tPA administration can result in angioedema. Angiotensin-converting enzyme (ACE) inhibitors can also lead to increased levels of bradykinin and appear to be a risk factor for tPA-associated angioedema. A literature review was conducted to examine previous cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…ACE inhibitors are the most recognized predisposing factors for OA. [ 7 ] One hypothesis is a bradykinin-mediated pathway in which RT-PA hydrolyzes plasminogen to plasmin, which in turn activates the kinin pathway and increases bradykinin production. [ 8 ] Bradykinin is a potent pro-inflammatory and pro-edematous peptide that increases vascular permeability and vasodilatation, leading to angioedema.…”
Section: Discussionmentioning
confidence: 99%
“…ACE inhibitors are the most recognized predisposing factors for OA. [ 7 ] One hypothesis is a bradykinin-mediated pathway in which RT-PA hydrolyzes plasminogen to plasmin, which in turn activates the kinin pathway and increases bradykinin production. [ 8 ] Bradykinin is a potent pro-inflammatory and pro-edematous peptide that increases vascular permeability and vasodilatation, leading to angioedema.…”
Section: Discussionmentioning
confidence: 99%
“…Angioedema after tPA infusion is a known complication and has an incidence of approximately 1-5%. 7 Additionally, it is suggested that angioedema will typically occur on the contralateral side of the ischemic hemisphere. 6 Several studies have proposed certain predisposing factors to the development of angioedema with the administration of tPA.…”
Section: Discussionmentioning
confidence: 99%